Application of the Kumon Learning Model with Active Learning Strategies to Improve Learning Outcomes in Simulation and Digital Communication - Alla’ Junia Nurdin; Agus Efendi; Endar Supri Wihidayat (Pendidikan Teknik Informatika dan Komputer, Universitas Sebelas Maret, 2019)
The application of the Kumon learning model with Active Learning Strategy aims to improve learning outcomes for students of class X AXIOO SMK N 5 Surakarta on simulation and digital communication. The research began because some students experienced difficulties in learning. This research took place in two cycles, data collection techniques which consisted of tests, observations, interviews, and documentation. Data validity test techniques which used data source triangulation techniques and triangulation methods. Quantitative descriptive analysis model was used to analyse the data. The improvement can be proven by the values of cognitive, affective and psychomotor aspects in each cycle. In the first cycle, the cognitive value of students reached 75% completeness, the completeness of students in the psychology value was 60.71%, while affective value reached 72% completeness, and final score 75 could be categorized as good. In the second cycle, the cognitive value increased 82.14% of completeness, while the psychomotor completeness was 85.71% and the affective value increased to 84% completeness and final score 90 can be categorized very well.Keywords: active learning, classroom action research, kumon, learning outcomes, simulation and digital communication